Analysis of Geomagnetic Storms Using Wavelet Transforms - Adhikari, B.; Khatiwada, R.; Chapagain, N. P. (Journal of Nepal Physical Society, 2017)
Geomagnetic storms are recognized as a worldwide decrease of the horizontal component of the Earth’s magnetic field measured at middle- and low-latitude magnetometers. The variations in the geomagnetic field during geomagnetic storms can be reproduced by changes in the interplanetary magnetic field and the solar wind velocity. Wavelet analysis, a useful statistical tool for analyzing variability has been used for this study. Wavelet transforms seem to be suited to analyze short-lived high-frequency phenomena such as discontinuities (shocks) in signals and transient structures. Wavelet analysis employed in the present work helps to decompose the time series of scales of interplanetary magnetic field (IMF-Bz) into different scales. To identify geomagnetic storms, the equatorial index, SYM-H has been used. The increase of wavelet coefficient amplitudes of the IMF-Bz is well correlated with the arrival of the shock and sheath region Journal of Nepal Physical Society Volume 4, Issue 1, February 2017: 119-124